EDUKASI DAN PEMERIKSAAN KESEHATAN MASYARAKAT DI KAMPUNG BATU BUSUK KECAMATAN PAUH KOTA PADANG - Saptino Miro; Najirman Najirman; Dinda Aprillia; Fauzar Fauzar; Andry Kurniawan; Zelly Dia Rofinda (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2022)
Non-contagious diseases have continued to increase over the years. In 2016, about 71 percent of the world's causes of death were non-contagious diseases (NCD) that kill 36 million people annually. Major risk factors of the non-contagious disease are metabolic factors, behavioral factors, and environmental factors. Riskesdas 2018 shows the prevalence of non-contagious diseases increasing compared with Riskesdas 2013, including cancer, stroke, chronic kidney disease, diabetes mellitus, and hypertension. The purpose of this activity is to increase promotive and preventive effort and education in the community, as well as improved screening and early detection through health education, blood pressure, blood sugar, cholesterol levels, and the abdominal ultrasound of society in Kampung Batu Busuk, Kelurahan Limau Manis, Kecamatan Pauh, Padang on Saturday, November 13th, 2021. Such activities include medical examinations of blood pressure, cholesterol, blood sugar, and abdominal ultrasound. From the activity of the examination of the health of 41 persons, 13 were hypertensive, 2 (32%) were hyperglycemia, 24 (58.5 percent) were dyslipidemia, and 6 were fatty liver. To counter the problem of non-contagious diseases, comprehensive and holistic intervention efforts must be made, that is, promotive, preventive, curative, and rehabilitative, as a unified continum of care. Disorders that are not treatable during an activity are recommended for treatment at a nearby health care center.